2012
DOI: 10.1039/c2cp40564d
|View full text |Cite
|
Sign up to set email alerts
|

Near room temperature dielectric transition in the perovskite formate framework [(CH3)2NH2][Mg(HCOO)3]

Abstract: We report that the hybrid organic-inorganic compound [(CH3)2NH2][Mg(HCOO)3] shows a marked dielectric transition around Tt∼ 270 K, associated to a structural phase transition from SG R3[combining macron]c (centrosymmetric) to Cc (non-centrosymmetric). This is the highest Tt reported so far for a perovskite-like formate that is thus a promising candidate to display electric order very close to room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
124
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 23 publications
9
124
0
1
Order By: Relevance
“…6. This result suggests an existence of the first-order phase transition around 270 K and is consistent with the results of dielectric and DSC measurements by Pato-Doldán et al [10]. The existence of two spin-lattice relaxation times T 1S and T 1L in 200 < T/K < 270 can be explained as the coexistence of the highand low-temperature phases.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…6. This result suggests an existence of the first-order phase transition around 270 K and is consistent with the results of dielectric and DSC measurements by Pato-Doldán et al [10]. The existence of two spin-lattice relaxation times T 1S and T 1L in 200 < T/K < 270 can be explained as the coexistence of the highand low-temperature phases.…”
Section: Resultssupporting
confidence: 89%
“…It is expected that these properties are triggered by freezing of the motion of the organic cation. We have applied nuclear magnetic resonance (NMR) spectroscopy to study the relation between the cationic motion and physical properties of the metal-organic perovskites and have identified the ring-puckering motion of the azetidinium ion in [(CH 2 ) 3 3 ] were reported by Pato-Doldán et al [10]. This compound crystallizes in a central space group R3c in the room temperature phase [10,11].…”
Section: Nh 2 ][M(hcoo)mentioning
confidence: 89%
“…37,44,45 Substitution at the A-site allows tuning of the ferroelectric polarisation, 46 whereas variation in transition-metal affects the ferroelectric transition temperature T c . 38,47 In this context, framework flexibility may have important implications for A-site orientational ordering and/or mechanisms of accommodating the large strains induced during ferroelectric/paraelectric switching. So this study has the additional relevance beyond establishing compositionproperty relationships of exploring the role of flexibility in ferroelectric MOFs.…”
Section: Nh 2 ][M(hcoo)mentioning
confidence: 99%
“…But the broader family is also of significance from a functional materials viewpoint. ABX 3 formates exhibit a variety of useful properties, including ferroelectricity, [36][37][38] ferroelasticity, 39 and even multiferroic behaviour. [40][41][42][43] Composition/property studies of the ferroelectric response in the A I = NH + 4 or (CH 3 ) 2 NH 2 + members points to the different possible effects of substitution on the alkylammonium site and the transition-metal site.…”
Section: Nh 2 ][M(hcoo)mentioning
confidence: 99%
“…[18][19][20] It was in this context that we sought to explore cation distributions in the mixed-metal formate perovskites [Gua]Cu x M 1−x (HCOO) 3 (Gua + = C(NH 2 ) + 3 ; M = Mn, Zn, Mg). It has been known for some time that many formate perovskites show relaxor-like dielectric behaviour, [21][22][23] which is usually associated with glassy dynamics of the organic (A-site) cation. 24,25 Indeed a recent 13 C NMR study of [(CH 3 ) 2 NH 2 ]Zn(HCOO) 3 even demonstrated the spontaneous formation of fluxional PNRs during the onset of ferroelectric order.…”
mentioning
confidence: 99%